Triadic interactions in families with preterm children: a comparative study with children born at term - Gatta M; Miscioscia M; Svanellini L; Brianda ME; Guerra G; Battistella PA; Simonelli A (Neuropsychiatric Disease and Treatment, 2017)
Michela Gatta,1,2 Marina Miscioscia,2,3 Lorenza Svanellini,2 Maria Elena Brianda,3 Giada Guerra,3 Pier Antonio Battistella,2 Alessandra Simonelli3 1Childhood Adolescence Family Unit AULSS 6 Veneto, 2Department of Women’s and Children’s Health, 3Department of Developmental Psychology and Socialization, University of Padova, Padova, Italy Abstract: The relationship between parents and infants born preterm is multifaceted and could present some relational patterns which are believed to predict psychological risk more than others. For example, insensitive parenting behavior has been shown to place very preterm children at greater risk of emotional and behavioral dysregulation. The main objective of this study was to compare the quality of family interactions in a sample of families with preterm children with one of the families with at-term children, exploring possible differences and similarities. The second aim of this research was to consider the associations among family interactions and parental empowerment, the child’s temperament, parenting stress, and perceived social support. The sample consisted of 52 children and their families: 25 families, one with two preterm brothers with preterm children (mean 22.3 months, SD 12.17), and 26 families with children born at term (mean 22.2 months, SD 14.97). The Lausanne Trilogue Play procedure was administered to the two groups to assess the quality of their family interactions. The preterm group was also administered the Questionari Italiani del Temperamento, the Family Empowerment Scale, the Multidimensional Scale of Perceived Social Support, and the Parenting Stress Index – Short Form. Differences in the quality of family interactions emerged between the preterm and at-term groups. The preterm group showed significantly lower quality of family interactions than the at-term group. The parenting stress of both parents related to their parental empowerment, and maternal stress was also related to the partner’s parental empowerment. Social support had a positive influence on parenting stress, with maternal stress also related to perceived social support from the partner, which underscores the protective role of the father on the dyad. Keywords: family interactions, preterm birth, parenting, Lausanne Trilogue Play